Intergenerational Public Goods Approach for Decentralizing Forestry Affairs - Mujibur Rahman Khairul Muluk; Y R Priyo Nugroho (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Forest, as one of determinant life support and people’s prosperity resources, tends to deteriorate, and as the effect, its existence must be optimally and sustainably maintained. Accommodating the dynamic of the people’s aspiration and participation is a must in maintaining the sustainability of the forest. The paper attempts at analyzing the process of decentralization of forestry affairs in Blora, Central Java and all stakeholder’s opinion about forest for the present and future generation. The findings show that the Central Government focuses on the efficiency and externalities as consideration in renewing delegation of authority in forestry affairs. However, that was not enough. There should be a fundamental exchange in the stakeholders’ perspectives. The stakeholders should start seeing forest as intergenerational public goods instead of common pool goods. Intergenerational public goods means that forest should be managed not only for present generation interest but also for future generation needs. Sustainable forest management is needed for intergenerational benefit. The principles of sustainability should be added to the existing principles in decentralization in order to realize sustainable forest management.